Implementasi Publikasi Informasi Program Sosial PPID Dinas Sosial Provinsi Banten - Nurul Rif’ah; Anti Wulan Agustini (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
Community service is a manifestation of the implementation of the Tri Dharma of Higher Education, oriented toward providing direct benefits to society. In the field of social services, community service activities play an important role in supporting public information transparency, particularly in the dissemination of social assistance programs and social welfare services. This article discusses the implementation of information publication for social programs managed by the Information and Documentation Management Officer (PPID) of the Social Affairs Office of Banten Province as part of a community service activity.The implementation method employed a descriptive qualitative approach through field activities conducted within the Community Work Practice (KKP) program. Data were collected through observation, interviews, and document review. The results of the community service implementation indicate that the PPID of the Social Affairs Office of Banten Province has utilized various communication media, both digital and non-digital, to publish information on social programs, thereby facilitating public access to information. This community service activity has had a positive impact on increasing transparency, accountability, and public trust in the implementation of social programs. Nevertheless, efforts to optimize the management and dissemination of information still need to be enhanced in order to reach all segments of society more effectively.